Pengaruh buku teks IPA terpadu tipe connected tema indera pendengaran dan sistem sonar pada makhluk hidup terhadap hasil belajar siswa kelas VIII SMPN 13 Padang - Aris Alfikri; Ratnawulan Ratnawulan; Gusnedi Gusnedi (Universitas Negeri Padang, 2019)
Achievement of student learning outcomes in science learning is still not as expected. The causal factors regarding teacher education background, integrated learning models that have not been applied optimally, students' difficulties in connecting science material, and science learning resources related to material integration by the 2013 curriculum. Speculation of solutions to this problem by using The Integrated Science Textbook Type Connected. This research is concerned with studying and the relationship of The Integrated Science Textbook Type Connected to Student Learning Outcomes of second grade students of SMPN 7 Padang.This type of research is quasi-experimental research using Posttest Only Control Group Design research scheme. The population in this study were all second-year students of SMPN 7 Padang in 2018/2019 academic year. Sampling is done by combining Purposive Sampling and Cluster Random Sampling techniques. The research instrument consisted of posttest sheets and performance evaluation sheets. The data in this research were analyzed using descriptive analysis, two similarity tests, simple linear regression, and correlation test.The results showed that there were significant differences in student learning outcomes using The Integrated Science Textbook Type Connected and those that did not use, and there was a significant relationship between the application of the science textbooks to student learning outcomes for knowledge and skill competencies at the 0.05 level. Product moment correlation for knowledge competence obtained rxy value of 0.49, stated the level of moderate relationships and skills of 0.64 with a strong relationship level. In the calculation of the coefficient of determination obtained the percentage of contribution of The Integrated Science Textbook Type Connected to the aspect of knowledge 23.75%, and the aspect of skills 43.55%.